Genetic diversity analysis of high oil maize inbred lines (Zea mays L.) - Nath, Ravindra; Rakshit, S.; Lodha, P.; Chaudhary, V.; Kumar, B.; Sharma, P.; Dass, S. (Annals of Agricultural Research, 2016)
The availability of reliable genetic diversity in maize inbred lines is liable for identifying heterosis in hybrid breeding. In the present study, 20 high oil inbred lines of maize, 46 microsatellite (SSR) and 28 RAPD markers were used to compare the molecular diversity. The 46 SSR markers resulted in to 182 alleles, while 28 RAPD markers produced 141 alleles. The polymorphism information contents (PIC) and discriminatory rate (DR) for SSR markers ranged between 0.45 to 0.84 and 0.40 to 0.86, respectively. For RAPD markers PIC value ranged from 0.11 to 0.97. The genetic similarity expressed as Jaccord’s similarity coefficients, for SSR and RAPD markers ranged between 0.09 to 0.44, and 0.40 to 0.68, respectively. The data of both the markers were employed to obtain dendogram with agglomerative Unweighted Pair Group Method using Arithmetic Average (UPGMA). SSR dendogram resulted in three main clusters and these clusters were further divided into seven sub clusters. Cluster 1 had five genotypes, cluster 2 with 3 sub clusters contained 10 genotypes and cluster 3 with 2 sub clusters had 5 genotypes. RAPD dendogram showed 4 clusters containing 2, 11, 4 and 2 genotypes, respectively. The heterozygosity and genetic diversity based on SSR markers alone ranged from 0.05 to 0.55 and 0.49 to 0.84, respectively. The present study showed that RAPD markers were effective to validate pedigree data, while SSR markers were produce more information, uniallele and rare alleles and this study concluded that co-dominant markers are suitable for molecular diversity analysis.